Penilaian pembelajaran peserta program kelayakan profesional kepengetuaan kebangsaan - Kamaruzzaman Moidunny,; Norasmah Othman,; Siti Rahayah Ariffin, (penerbit ukm, 2010)
The purpose of this study is to evaluate the learning performance of National Professional Qualification for Headship(NPQH) participants, based on their gender and group. Evaluation of learning involved nine aspects: organizational leadership and management, curriculum management, co-curricular management, student affairs management, financial management, office administration management, environmental management and physical facilities, human resource management and development, and external relationship management. Achievement test scores were used as the instrument. The data were analyzed using mean and MANOVA. A total of 271 respondents participated in this study using stratified random sampling technique. Findings indicated the difference in learning performance in curriculum management for male and female participants. Findings also indicated differences in learning performance with regards to organizational leadership and management, student affairs management, environmental management and physical facilities, human resource management and development, and external relationship management, for graduate and non-graduate participants. The implications of these findings suggest that the NPQH training program should be continued. However, efforts to improve the learning performance need to be enhanced in order to meet the needs of the aspiring school managers in Malaysia.